Food safety regulation in Bangladesh, chemical hazard and some perception to overcome the dilemma - Islam, G.M.R. (2015)
This article focus on the problems arises in public health due to the presence of chemical hazard in food supply chain and supports require for food industry of Bangladesh in order to supply safe food to the end consumer. From the evidence it may be sated that in Bangladesh food safety rules and regulation not enough to deal with the problem. Now, the country is in difficult situation with chemical hazard in food stuff. Bangladesh authorities should develop: (a) adequate infrastructures including laboratory services for inspector; (b) as well as public awareness in order to manage the situation. However, strengthening infrastructures should include getting adequate trained personnel and expertise as well as tough enforcement.